RESPON MORFOLOGI DAN PRODUKSI TANAMAN KEDELAI (Glycine max L.) TERHADAP PENGGUNAAN BERBAGAI DOSIS ASAM SALISILAT DALAM CEKAMAN SALINITAS - Narayana, Ramadhan Cakra; Anwar, Syaiful; Karno, Karno (Universitas Tribhuwana Tunggadewi, 2023)
This study aimed to examine the effect of exogenous salicylic acid treatment and salinity stress on the morphology and seed yield of soybeans (Glycine max L.). The experimental design used a completely randomized design factorial with four replications. The first factor was Salicylic Acid with four different dosages, namely 0 ppm, 100 ppm, 200 ppm, and 300 ppm. The second factor was Salinity Stress with two levels, 0 dS/m, and 5 dS/m. The observed parameters were root volume, plant height, total leaf area, root shoot ratio, and seed weight. The result showed that plant height, total leaf area, root volume, and root-shoot ratio were not significantly affected by salicylic acid treatment. Seed weight showed an increase in salicylic acid treatment. Salinity stress reduced all morphological size and seed yields of soybeans significantly.